2016
DOI: 10.1111/crj.12521
|View full text |Cite
|
Sign up to set email alerts
|

Oki stent application in different indications: Six cases

Abstract: Oki stents can safely be used for many clinical conditions. Patients benefit greatly from stenting; however, two of our cases died due to infection, and one case died due to malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Several studies have shown the efficacy of silicone or metallic stents for the management of AC after LT [ 20,23,26,[29][30][31][32], but to our knowledge, this is the first study evaluating the role of OSMBS on a large patient population. Our study, along with previously reported data from case series [10][11][12][13], lends support to the feasibility, safety, and efficacy of these stents with a successful placement in 90%, with objective improvement in pulmonary function studies. The anatomy of the SC on both sides is more complex than that of the main carina.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several studies have shown the efficacy of silicone or metallic stents for the management of AC after LT [ 20,23,26,[29][30][31][32], but to our knowledge, this is the first study evaluating the role of OSMBS on a large patient population. Our study, along with previously reported data from case series [10][11][12][13], lends support to the feasibility, safety, and efficacy of these stents with a successful placement in 90%, with objective improvement in pulmonary function studies. The anatomy of the SC on both sides is more complex than that of the main carina.…”
Section: Discussionsupporting
confidence: 84%
“…Management of long-term complications from customized bifurcated stent (CBS) on SC in patients with longer life expectancy remains unclear [9]. To date, only 4 publications [10][11][12][13] of Y-stents placed for posttransplant AC have been reported. One study focused on T-tube placement on the right anastomosis and suggested a significant improvement of the FEV1, albeit with a high rate of stent migrations (33%) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 76% abnormal bronchoscopic findings, it was observed that most of the pathologies were in the right endobronchial system specifically the right main bronchus. Pathologies in the right endobronchial system and lung are a common finding in literature, especially in the adult population, mainly because of the angulation and length of the right main bronchus [ 2 , 3 ]. The most commonly diagnosed condition in our patients was cancer of the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy has advanced over the past decades from just a diagnostic tool to interventional and endobronchial ultrasound (EBUS) bronchoscopy [ 1 ]. It is a commonly performed procedure by pulmonologists, thoracic surgeons, Ear Nose and Throat (ENT) surgeons and anesthetists for different indications, including but not limited to diagnosis, cancer staging, foreign body removal, airway stenting, dilatation, intubation, management of difficult airway and inhalation injuries [ 2 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different stents (SEMS, silicon, hybrid, and biodegradable stents) have been proposed, but no single method has demonstrated clear superiority and procedure decision mainly depends to single institutions and operators experience. 1,6 Some complex BS even need open surgical approaches. 5 The use of this innovative stenting procedure with a modified endobronchial valve for emphysema, herein presented, appears a suitable option in patients with short segmental and subsegmental BS after LT.…”
mentioning
confidence: 99%